2014
DOI: 10.1038/gt.2014.66
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficiency of mesenchymal stromal cell-mediated CD-MSC/5FC therapy in human melanoma xenograft model

Abstract: Mesenchymal stromal cells (MSC) can be exploited as cellular delivery vehicles for the enzymes converting non-toxic prodrugs to toxic substances. Because of their inherent chemoresistance, they exert potent bystander and antitumor effect. Here we show that the human adipose tissue-derived MSC expressing fusion yeast cytosine deaminase::uracil phosphoribosyltransferase (CD-MSC) in combination with 5-fluorocytosine (5FC) mediated a long-term tumor-free survival in the 83.3% of tumor-bearing animals. CD-MSC/5FC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 57 publications
2
52
0
1
Order By: Relevance
“…In order to diminish the viability to less than 90%, there had to be the 20% of the CD-MSC present at the culture initiation. This outcome corresponds to the data already published, when 20% of CD-MSC/5FC were able to significantly reduce the tumor growth and achieve a complete tumor regression in the 83.3% of the animals in a long-term experiment [12]. Although the 10% of the therapeutic cells significantly reduced a spheroid volume and achieved the 75% inhibition of the viability, this was sufficient for the tumor inhibition but not for the complete tumor eradication in animals.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In order to diminish the viability to less than 90%, there had to be the 20% of the CD-MSC present at the culture initiation. This outcome corresponds to the data already published, when 20% of CD-MSC/5FC were able to significantly reduce the tumor growth and achieve a complete tumor regression in the 83.3% of the animals in a long-term experiment [12]. Although the 10% of the therapeutic cells significantly reduced a spheroid volume and achieved the 75% inhibition of the viability, this was sufficient for the tumor inhibition but not for the complete tumor eradication in animals.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the therapeutic-to-target cell ratio 1:20 CD-MSC/5FC:A375 decreased in vitro by 90% viability as determined by the standard MTS viability assay. These data correlated with the outcomes from the fluorimetric evaluation of the bystander effect and luminometric viability assay based on the ATP levels in the treated cells [12]. In contrast, it was necessary to co-inject 10% of therapeutic CD-MSC cells with the target melanoma A375 cells in order to achieve significant delay in the tumor onset.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…After systemic administration of therapeutic cells we observed signifi cant inhibition of growth of subcutaneous xenotransplants derived from colorectal cancer (12) or melanoma (13). In this melanoma model we also demonstrated that more than 80 % of treated mice survive for long-term without relapse (14).…”
Section: Gene Therapy Mediated By Mesenchymal Stromal Cellsmentioning
confidence: 75%
“…With the exception of gene therapy, 5-fluorocytosine (5-FC) and Na 131 I have also been used in cancer therapy combined with gene therapy: Kucerova et al (25) utilized CD-mesenchymal stromal cells/5-FC as an effective gene therapeutic tool. Zimmer et al (26) also used Na 131 I to mediate radiochemical therapy.…”
Section: Introductionmentioning
confidence: 99%